Compassionate use of recombinant human IL‐7‐hyFc as a salvage treatment for restoring lymphopenia in patients with recurrent glioblastoma - Stephen Ahn; Jae‐Sung Park; Heewon Kim; Minkyu Heo; Young Chul Sung; Sin‐Soo Jeun (Cancer Medicine, 2023)
Abstract Purpose Addressing lymphopenia in cancer patients has been suggested as a novel immunotherapeutic strategy. As interleukin‐7 (IL‐7) is necessary for proliferation of lymphocytes and to increase total lymphocyte count (TLC), IL‐7 therapy has been attempted in various cancers. Here, we describe the clinical results of treatment of recurrent glioblastoma (GBM) with a long‐acting engineered version of recombinant human IL‐7 (rhIL‐7‐hyFc). Methods This prospective case series based on compassionate use was approved by the Ministry of Food and Drug Safety in South Korea. Primary outcomes were safety profile and TLC. Secondary outcomes were overall survival (OS) and progression‐free survival (PFS). Results Among the 18 patients enrolled, 10 received rhIL‐7‐hyFc with temozolomide, 5 received rhIL‐7‐hyFc with bevacizumab, 1 received rhIL‐7‐hyFc with PCV chemotherapy, and 2 received rhIL‐7‐hyFc alone. Mean TLC of the enrolled patients after the first rhIL‐7‐hyFc treatment increased significantly from 1131 cells/mm3 (330–2989) at baseline to 4356 cells/mm3 (661–22,661). Higher TLCs were maintained while rhIL‐7‐hyFc was repeatedly administered. Median OS and PFS were 378 days (107–864 days) and 231 days (55–726 days), respectively. Conclusion Our study reports that IL‐7 immunotherapy can restore and maintain TLC during treatment with various salvage chemotherapies in recurrent GBM patients without serious toxicity.